Corona Virus Disease 2019 patients with different disease severity or age range: A single-center study of clinical features and prognosis. Issue 49 (4th December 2020) - Ren, Lingyun; Yao, Dan; Cui, Zuowei; Chen, Shanshan; Yan, Hong
Abstract : Abstract: This study aimed to describe clinical characteristics and prognosis of Corona Virus Disease 2019 (COVID-19) patients, and to compare these features among COVID-19 patients with different disease severity or age range. Totally, 129 COVID-19 patients were retrospectively enrolled, and the information about demographics, comorbidities, medical histories, clinical symptoms, and laboratory findings at the time of hospital admission were collected. Meanwhile, their clinical outcomes were recorded. According to the fourth version of the guidelines on the Diagnosis and Treatment of COVID-19 by the National Health Commission of China, patients were divided into subgroups according to disease severity (moderate and severe/critical) or age (<40 years, 40–64 years and ≥65 years). In total patients, the most common clinical symptoms were fever and cough (all incidences over 50%). Other common clinical symptoms included tiredness/anorexia, shortness of breath, dyspnea, aching pain, expectoration, diarrhea, shivering, and nausea/vomiting. The mortality rate was 5.4%, and the median value of hospital stay was 16.0 (11.0–23.0) days. Subgroup analyses disclosed that severe/critical patients exhibited increased neutrophil count, neutrophils, C-reactive protein, calcitonin, alpha-hydroxybutyric dehydrogenase, lactate dehydrogenase, aspartate aminotransferase, gamma-glutamyl transferase, creatinine, and D-dimer levels, and more deaths compared with that in moderate patients. Regarding age, it correlated with more common fever, higher levels of red blood cell, neutrophil count, lymphocyte count, neutrophils, red cell volume distribution width standard deviation-coefficient of variation, calcitonin, alpha-hydroxybutyric dehydrogenase, Creatine Kinase, aspartate aminotransferase, gamma-glutamyl transferase, and D-dimer, raised death rate and prolonged hospital stay. Our findings provide valuable evidence regarding clinical characteristics and prognosis of COVID-19 patients to help with the understanding of the disease and prognosis improvement.